Analisis Perbandingan Unjuk Kerja Sistem Penyeimbang Beban Web Server dengan HAProxy dan Pound Links - Dite Ardian; Adian Fatchur Rochim; Eko Didik Widianto (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2013)
The development of internet technology has many organizations that expanded service website. Initially used single web server that is accessible to everyone through the Internet, but when the number of users that access the web server is very much the traffic load to the web server and the web server anyway. It is necessary for the optimization of web servers to cope with the overload received by the web server when traffic is high. Methodology of this final project research include the study of literature, system design, and testing of the system. Methods from the literature reference books related as well as from several sources the internet. The design of this thesis uses Haproxy and Pound Links as a load balancing web server. The end of this reaserch is testing the network system, where the system will be tested this stage so as to create a web server system that is reliable and safe. The result is a web server system that can be accessed by many user simultaneously rapidly as load balancing Haproxy and Pound Links system which is set up as front-end web server performance so as to create a web server that has performance and high availability.